THE IMPLEMENTATION OF THE RISK-ORIENTED TRAINING APPROACH IN THE UNIVERSITIES WITH SPECIFIC EDUCATIONAL CONDITIONS - Artemov, V.; Lytvynenko, N. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The features of the risk-oriented approach when used for educational purposes in higher education institutions with specific learning conditions are revealed. The ways of the risk-oriented thinking formation among employees of security structures are determined. It is assumed that the semantic space associated with the moral proper, includes the following concepts: "permissible", "unacceptable", "compulsory". The aforementioned triad is recommended to be supplemented by the notion "necessarily". The necessary actions should include actions related to the risk of losing freedom, health, and sometimes even death, in connection with forced or involuntary acts to carry out moral duty, order, law. Such actions are often endowed with a higher status in the hierarchy of official actions, are considered to be granted the highest degree of moral approval and, even, admiration. At the same time, those who carry out the necessarily actions, as a rule, perceive their actions as just the performance of official duty. Therefore, the commission of actions related to professional risk becomes a duty only because of the special self-consciousness inherent in the military and law enforcement officers. The higher education institutions with specific educational conditions should be aimed at improving the system of moral education of security officers, the comprehensive involvement of the latest ideas, methods and means of modern pedagogy, based on the deontological potential of the competent approach in the professional training system. The process of the risk-oriented thinking formation for future employees of security organs should be carried out subject to the use of the modern legal and regulatory framework on safety and health of the European Union, which will enhance their competitiveness in the modern labor market.